Effect of Ethanol Extract and Fractions of Saluang Balum Root Lavanga Sarmentosa (Blume) Kurz) on Aphrodisiac Activity and Spermatogenesis in Hyperglicemia Rats - Dwiannur, Febriandi Ramadhan; Peranginangin, Jason Merari; Saptarini, Opstaria (Jurnal Ilmiah Kesehatan (JIKA), 2024)
High blood glucose levels or hyperglycemia can increase reactive oxygen species (ROS). Complications of secondary diabetes mellitus in the form of sexual dysfunction and impaired fertility in men. This is one of the causes of decreased sexual desire and sperm count, which can cause infertility in men. Saluang balum root (Lavanga sarmentosa (Blume) Kurz) with flavonoid, steroid, and tannin compounds is a traditional medicine that has the potential as an aphrodisiac and spermatogenesis. The purpose of this study was to obtain a histological picture of the seminiferous tubules, a decrease in blood glucose levels, aphrodisiac activity, and spermatogenesis. This study used 35 male wistar rats which were divided into 7 groups, normal group, negative control (CMC Na 1%), positive control (pasak bumi), ethanol extract of saluang balum root at a dose of (225 mg/kgBW), n-hexane fraction. (19.81 mg/kgBW), ethyl acetate fraction (64.5 mg/kgBW) and water fraction (140.67 mg/kgBW). All of these groups were induced by alloxan (100 mg/kgBW), except the normal group. The extracts and fractions were given for 14 days, then observed a decrease in blood glucose levels, aphrodisiacs, spermatogenesis and histological features in the seminiferous tubules. The results showed that the extract and fractions of saluang balum root had reduced blood glucose levels, aphrodisiac and spermatogenesis in hyperglycemic rats.